2004
DOI: 10.1111/j.1524-4725.2004.30432.x
|View full text |Cite
|
Sign up to set email alerts
|

Why Are There Differences in the Perceived Safety of Office-Based Surgery?

Abstract: The medical and legislative community should seek to scientifically examine office surgery. Overregulation or loss of office surgery would have a tremendous impact on the management of skin cancers and the delivery of quality cosmetic and laser surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Even though mortality related to the ambulatory surgical setting is rare, this indicator has been used to flag potential quality problems associated with ambulatory surgery [6,7,9,25]. Other researchers have also used mortality as an outcome for comparing quality of care provided in the outpatient setting [8,12,26,27]. We used 7-day indicators since, as a shorter measure, it can reduce the effects of extraneous factors unrelated to outpatient procedures [6].…”
Section: Outcome Variablementioning
confidence: 99%
“…Even though mortality related to the ambulatory surgical setting is rare, this indicator has been used to flag potential quality problems associated with ambulatory surgery [6,7,9,25]. Other researchers have also used mortality as an outcome for comparing quality of care provided in the outpatient setting [8,12,26,27]. We used 7-day indicators since, as a shorter measure, it can reduce the effects of extraneous factors unrelated to outpatient procedures [6].…”
Section: Outcome Variablementioning
confidence: 99%
“…In short, the data suggest that dermatologic surgery and liposuction under dilute local (tumescent) anesthesia were associated with a very low incidence of adverse events. [6][7][8][9][10][11] Specifically, prospective data from 7 years of mandatory reporting in Florida indicated that dermatologists had not been responsible for a single death. In addition, there were no deaths or hospital transfers associated with liposuction under dilute local anesthesia.…”
Section: Malpracticementioning
confidence: 98%
“…32 Most individual specialty societies, however, found themselves constrained by insufficient numbers of existing evidence-based guidelines, the high cost of measure development, limited technical expertise as they tried to recruit staff capable of developing measures, and concerns from members who feared the inappropriate use of developed measures by managed care organizations. 10 Those specialty societies with early successes were able to devote significant resources to creating organized infrastructures that engaged membership and simultaneously developed guidelines and linked them to measures with well defined methods for data collection. 10 To assist specialty societies in overcoming barriers and developing physician-level performance measures, the AMA formed the PCPI in 2000.…”
Section: Malpracticementioning
confidence: 99%
See 1 more Smart Citation
“…It was found that hospital-based liposuction had three times the rate of malpractice settlements when compared with office-based liposuction surgery. [3537]…”
Section: Safety Of Tumescent Liposuctionmentioning
confidence: 99%